Health, life and rights: a discourse analysis of a hybrid abortion regime in Tanzania - Richard Sambaiga; Haldis Haukanes; Karen Marie Moland; Astrid Blystad (BMC, 2019)
Abstract Background Unsafe abortion continues to be a major hazard for maternal health in Sub-Saharan Africa, where abortion remains highly controversial and access to safe abortion services is unequally distributed. Although national abortion laws are central in indicating women's potential for accessing safe abortion services, the character of an abortion law may alone say little about national discursive abortion landscapes and access scenarios. The article calls for the study and problematization of the relationship between legal abortion frameworks on the one hand, and discourses surrounding abortion on the other, in an attempt to move closer to an understanding of the complexity of factors that influence knowledge about and access to safer abortion services. With the restrictive abortion law in Tanzania as a starting point, the paper explores the ways in which the major global abortion discourses manifest themselves in the country and indicate potential implications of a hybrid abortion regime. Methods The study combined a review of major legal and policy documents on abortion, a review of publications on abortion in Tanzanian newspapers between 2000 and 2015 (300 articles), and 23 semi-structured qualitative interviews with representatives from central institutions and organizations engaged in policy- or practical work related to reproductive health. Results Tanzania's abortion law is highly restrictive, but the discursive abortion landscape is diverse and is made manifest through legal- and policy documents and legal- and policy related disputes. The discourses were characterized by diverse frames of reference based in religion, public health and in human rights-based values, and as such reflect the major global discourses. Fairclough's concepts interdiscursivity and recontextualization were drawn upon to develop an understanding of how the concepts health, rights and life emerge across the discourses, but are employed in contrasting lines of argumentation in struggles for hegemony and legitimacy. Discussion and conclusions The paper demonstrates that a hybrid discursive regime relating to abortion characterizes the legally restrictive abortion context of Tanzania. We argue that such a complex discursive landscape, which cuts across the restrictive - liberal divide, generates an environment that seems to open avenues for enhanced access to abortion related knowledge and services.